Perbandingan Tutupan Lahan Spectral Indices Dan Class Signature Terhadap Pembentukan UHI Perkotaan Muna - Alan Apriyanto; Fitra Saleh; Nurgiantoro Nurgiantoro; Fitriani Fitriani; Jufri Karim (JAGAT (Jurnal Geografi Aplikasi dan Teknologi), 2023)
The urban area of Muna Regency is experiencing very rapid development, this triggers various problems, namely increasing population and urban development, increasing vehicles that affect air pollution and lack of provision of green open space in urban areas, so that these problems trigger the increase of Urban Heat Island (UHI) in Raha. This study aims to compare land cover classification methods based on spectral indices and class signature to the formation of UHI and also to find out how the distribution of Urban Heat Island in urban areas of Muna Regency. The materials used in this research are SHP of Muna Regency, BPS data in 2022, Landsat 8 OLI/TIRS image, and Google Earth image data. The methods used in this research are Spectral Indices and class signature. The results of this study show that the area of spectral indices analysis in the form of Normalized Difference Built-Up Index (NDBI) is 2052.29 ha. As for the class signature, it can be seen in the area of built-up land, which is 1533.65 ha. The area is an urban area that has many buildings which are UHI distribution areas. The distribution of UHI in Raha Urban Area shows that the area affected by UHI is dominated by the Katobu Sub-district area which is the center of Raha Urban Area with a temperature of 25.92 - 32.36°C.